Introducing social theory. - Jones, Pip (Polity Press., 2011)
This revised edition of Pip Jones's extremely popular introduction to social theory, now benefiting from the collaboration of Shaun Le Boutillier and Liz Bradbury, has been carefully and thoroughly updated with the latest developments in this continually changing field. Written in a refreshingly lucid and engaging style, Introducing Social Theory provides readers with a wide-ranging, well organized and thematic introduction to all the major thinkers, issues and debates in classical and contemporary social theory.